2018
DOI: 10.1111/1744-9987.12654
|View full text |Cite
|
Sign up to set email alerts
|

Serum Endocan Levels are Associated With Paraoxonase 1 Concentration in Patients With Chronic Kidney Disease

Abstract: Endocan is a soluble proteoglycan released by the vascular endothelium. The increase of its serum levels is associated with inflammation, endothelial dysfunction and cardiovascular events in patients with chronic kidney disease (CKD). We studied the association of serum endocan with the lipid profile of 105 CKD patients with dyslipidemia, divided in two groups, non-dialyzed (CKD, N = 57) and hemodialysis (HD, N = 48) in comparison with 30 normal controls (NC). We also analyzed endocan in relation with the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
1
11
0
1
Order By: Relevance
“…Su et al observed that serum ESM1 levels may reflect the degree of chronic renal allograft injury, and there in vitro study showed that tumor necrosis factor-α (TNF-α) induces high expression of ESM1 and Transforming growth factor-beta 1 (TGF-β1) in human umbilical vein endothelial cells [ 25 ]. Samouilidou et al found that a high level of serum ESM1 was positively associated with low density lipoprotein cholesterol (LDL-C), total cholesterol, and downregulation of paraoxonase (PON) in CKD patients [ 26 ]. In non-dialysis chronic kidney disease patients (stage 5), circadian heart rate variability correlates positively with serum ESM1 concentration [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Su et al observed that serum ESM1 levels may reflect the degree of chronic renal allograft injury, and there in vitro study showed that tumor necrosis factor-α (TNF-α) induces high expression of ESM1 and Transforming growth factor-beta 1 (TGF-β1) in human umbilical vein endothelial cells [ 25 ]. Samouilidou et al found that a high level of serum ESM1 was positively associated with low density lipoprotein cholesterol (LDL-C), total cholesterol, and downregulation of paraoxonase (PON) in CKD patients [ 26 ]. In non-dialysis chronic kidney disease patients (stage 5), circadian heart rate variability correlates positively with serum ESM1 concentration [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, factors related to endothelial dysfunction have increasingly been studied [ 39 ]. Endocan, playing a significant role in the regulation of cell adhesion and inflammatory disorders, has been shown to provide promising utilities in various kidney disease entities, such as acute kidney injury [ 42 , 43 ], chronic kidney disease [ 44 , 45 ], hemodialysis [ 46 ], peritoneal dialysis [ 47 , 48 ], renal transplantation [ 49 , 50 ], immunoglobulin A nephropathy [ 51 ], autosomal dominant polycystic kidney disease [ 52 ], and diabetic nephropathy [ 53 , 54 ]. It constitutes a potential biomarker in the prognosis and diagnosis of kidney diseases; however it has, so far, significant limitations ( Table 1 ).…”
Section: Endocan and Kidney Diseasesmentioning
confidence: 99%
“…The development of many diseases is associated with changes in PON3 levels. Increased serum levels of PON3 are linked with its protective role in chronic liver impairment [80], coronary artery disease [81], and chronic kidney disease [82]. In male mice, it has been demonstrated that an increase in liver PON3 activity significantly decreases atherosclerotic lesion formation and adiposity [83].…”
Section: Paraoxonase 3: In the Shadow Of His Younger Brothermentioning
confidence: 99%